Investigation of temperature-and-thermal conditions of heating metal in furnaces of cable wire plants of BMZ - V. V. Filippov (Литьë и металлургия, 2001)
The results of investigation of thermal operation of a patenting heating furnace are introduced, including problems of mathematical simulation of heating process, scaling minimization and fuel consumption.